Pemberdayaan Tenaga Kerja Lokal oleh PT. Waja Inti Lestari dalam Perspektif Peraturan Daerah Kolaka: Studi di Kecamatan Wolo - Mutiara (Institut Agama Islam (IAIN) Kendari, 2025)
This study aims to answer how the reality of empowering local workers at PT. Waja Inti Lestari, the obstacles faced in empowering local workers at PT. Waja Inti Lestari and the perspective of the Kolaka Regency Regional Regulation Number 19 of 2022 on empowering local workers at PT. Waja Inti Lestari.This type of research is empirical normative legal research. This research was conducted using a statutory approach and a case approach. With data collection techniques using observation techniques, interviews and documentation.The research results obtained show that: First, the reality of empowering local workers at PT. Waja Inti Lestari, has not run well and optimally because the company has not been able to provide education and job training to local workers. second, constraints in empowering local workers at PT. Waja Inti Lestari namely from the human resource itself, it means local workers who still lack skills and experience in working, until now PT Waja Inti Lestari has not been able to provide job training for local workers as has become the duties and responsibilities of the company, the three perspectives of the Kolaka Regency Regional Regulation on empowering local workers have not been carried out properly, because PT. Waja Inti Lestari has not been able to carry out its obligations in providing education and job training to local workers as a corporate social responsibility and duty. However, this has been clearly regulated in the Regional Regulation of Kolaka Regency Number 19 of 2022 concerning Empowerment of Local Workers. Keywords: Empowerment of Local Workers, PT. Waja Inti Lestari, Regional Regulation